Buoyancy and similarity of the swimming of Manta birostris(Elasmobranchii: Myliobatidae) with the flying cycle of Columba livia(Aves: Columbidae) - Meza Vélez, Iván (2013)
The physics of flotation in Manta birostriswas analysed and the swimming of this species was compared with the flight cycle of the common pigeon Columba livia, in order to find similarities and differences in their locomotion patterns and the laws of physics driving them. It was showed that the cycleof M. birostris has three of the main four stages of pigeon’s flying cycle. A “Parachute effect” was also demonstrated, which give an advantage on ray´s locomotion. Moreover, it was described how torque concept is applied to turn of this species.